The Shackles of CEO Celebrity: Sociocognitive and Behavioral Role Constraints on “Star” Leaders - Lovelace, Jeffrey B.; Bundy, Jonathan; Hambrick, Donald C.; Pollock, Timothy G. (Academy of Management Review, 2018)
We set forth a new theory for understanding the consequences of CEO celebrity. The fulcrum of our theory is the reality that CEOs attain celebrity because they are cast into specific archetypes, rather than for their general achievements. We present a typology of common celebrity CEO archetypes (creator, transformer, rebel, savior) and then detail a model highlighting the consequences associated with attaining celebrity of a given type. These consequences include an array of sociocognitive outcomes, which, in turn, constrain celebrity CEOs to those behaviors associated with their particular celebrity archetype. The sociocognitive outcomes’ main effects are moderated by the role intensity of the specific archetype, the CEO’s degree of narcissism, and the temporal arc (rate of ascent and duration) of celebrity. Finally, we argue that the effects of CEO celebrity on firm performance are contingent on the continuity of external and internal contextual conditions. If conditions change appreciably, the celebrity CEO’s rigidities become severe liabilities, explaining the documented tendency for CEO celebrity to bring about, on average, unfavorable firm outcomes.